(untitled) (Senderos, 2023)
Research about urban inequalities pose a significant academic challenge when aiming at acquiring a better understanding and a more complex outlook on reality. This article seeks to analyze social precariousness in the Metropolitan Area Greater Resistencia (AMGR by its name in Spanish) for the year 2010. It was thus necessary to develop Precariousness Indicators -PI- by considering deficient categories that arise from the different dimensions proposed by INDEC 2010. Alternatives can be combined in a methodological essay, and the proposed research problem is therefore addressed through two spatial analysis techniques, segregation and spatial aggregation or grouping analysis. It was possible to establish the predominance of the center-periphery relationship in the distribution of social precariousness in the AMGR for the year 2010, both in the spatial behavior of segregation and in the results obtained from the spatial grouping analysis.